Enlightenment-pedagogical heritage of P.P. Chubinskogo. - Valentyna Kramar (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with educational-pedagogical activity of outstanding Ukrainianscientist, anthropologist, folklorist, lawyer, teacher - P.P. Chubinskogo in the late nineteenthcentury and its role in the revival of Ukrainian national education and culture. Key words: P. Chubynskyi, education, educational activities, spirituality, Sundayschools, Ukrainian culture, traditions.